El informe de contraloría general del estado para la investigación del delito de peculado. - Puente Yumiseba, Jesica Fernanda (2018)
The Office of the General Comptroller of the State is an institution of a technical nature, whose purpose is to control the management of public funds and legal persons that have resources from the Ecuadorian State, so it has various powers through the direction of audits in entities of the public sector and legal entities that have money from the State, determining administrative, civil and criminal responsibilities if applicable, failing to issue additional regulations within the scope of their powers and advise various state entities, as determined by the Art. 212 of the Constitution of the Republic of Ecuador, in accordance with the provisions of Article 31 of the Organic Law of the General Comptroller of the State. In the crime of embezzlement, the indications of criminal responsibility fall on the public servant and the people who act with a state authority, who has disposed of assets, money, documents or reports belonging to the State for their own benefit or that of third parties, these in turn are verified through a report prepared by the General Comptroller of the State, which clearly determines each of the facts that have incurred the official, this report in the criminal field is a requirement of process to research of the crime of embezzlement against the alleged suspect for the purpose of judging the conduct in which he incurred. This paper analyzes the relevant aspects of the report with indications of criminal responsibility issued by the General Comptroller of the State, while allowing to verify the legal effects produced by this report in the investigation of the crime of embezzlement, ending with a proposal to reform the Art 581 last paragraph of the Comprehensive Criminal Organic Code.